Chickpea processing to obtain a protein ingredient for the plant-based market - Caldeira, Rodrigo Fernandes; de Paiva Gouvêa, Lucas; Azevedo, Tatiana de Lima; Wilhelm, Allan Eduardo; Freitas de Sá, Daniela de Grandi Castro; Galdeano, Melicia Cintia; Felberg, Ilana; Antoniassi, Rosemar; Mellinger, Caroline Grassi; Lima, Janice Ribeiro (Frontiers in Food Science and Technology, 2025)
Chickpea (Cicer arietinum L.) is the third most cultivated and consumed pulses worldwide, after bean and pea, and is commonly commercialized in the form of seeds, flour or canned. Grains are rich in proteins with the potential to be an alternative source of protein for human nutrition. The use of pulse proteins is highly dependent on composition, functional and structural properties. The objective of this study was to determine the best processing parameters for the wet extraction of protein from chickpea, as well as to analyze the technical-functional properties and physical characteristics of the protein concentrate. The application of the concentrate in fish-like croquette was also evaluated. The processing route was carried out by alkaline extraction and acid precipitation of proteins where pH, stirring time, and solute:solvent ratio were evaluated. The best results for alkaline extraction were at pH 8.5, solute:solvent ratio of 1:12, and stirring time of 20 min. For acid precipitation, the best results were at pH 4.5 and stirring time of 10 min. The final protein concentrate presented 78% protein (dry basis) and a mass yield of 10.2%. Regarding techno-functional properties, the results for defatted flour (CF) and protein concentrate (CPC) were as follows: solubility (CF pH 3 = 7.60% and pH 9 = 83.82%; CPC pH 3 = 51.45% and pH 9 = 90.72%), water holding activity (CF = 2.18 g/g and CPC = 1.23 g/g), oil holding capacity (CF = 1.69 g/g and CPC = 1.59 g/g), foaming capacity (CF = 82.22% and CPC = 77.78%), foam stability up to 60 min (CF = 92.67% and CPC = 93.82%), emulsifying capacity (CF = 18.79 m2/g and CPC = 16.49 m2/g), emulsion stability (CF = 28.69 min and CPC = 36.64 min) and the lowest degree of gelation for CF (0.10 g/mL) and CPC (0.18 g/mL). As demonstrated in the sensory test, the overall acceptance, flavor, and texture of croquettes added CPC showed no differences when compared to croquettes added with commercial fava bean concentrate. CPC proved to be a promising protein alternative for the plant-based market.